The Comparison of the Ownership Structure at Different Level of the Financial Collapse in Listed Firms of Tehran Stock Exchange - Kangarlouei, Saeid Jabbarzadeh; ., Morteza Motavassel (Information Management and Business Review, 2012)
The main objective of this study is to compare ownership structure of different levels of collapse in listed companies of Tehran Stock Exchange (TSE). Study variables are the ownership structure that includes governmental ownership, private ownership (corporate ownership and individual ownership) and the different levels of collapse including latency stage, the stage of cash deficits and commercial and financial insolvency and complete collapse. Altman model (ZÂ´- Score) is used to predict the collapse of firm and Chi-Square test is used to test the research hypothesis. The study is the applied research and statistical population of study includes 96 collapse firms that are active in the TSE (subject to Business Law Article 141). Given the availability of financial information of distressed companies in 7 years between 2004-2010 years, a sample of 81 members was selected. The results show that the ownership structure of collapsed firms is independent from their different levels of collapse.